Perancangan Film Dokumenter “Parsan” Sebagai Apresiasi terhadap Sosok Parsan, Pelukis Poster Manual Bioskop Rajawali Purwokerto: - - Irma Suryani, Riri; Purnamasari, Dwi Chandra; Yulius, Yosef (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
As technology develops rapidly from era to era, who would have thought that there would still be people who maintain the traditional style in conveying their messages. Parsan, is a traditional poster painter at the Rajawali Cinema, Purwokerto, who has been dedicating himself as a film poster painter for decades. The planning of this documentary film is an effort to appreciate the figure of Parsan. Documentary Film is a film that contains data, facts and actual events about the life and daily life of Parsan, a 57 year old man at Rajawali Cinema Purwokerto which has been established since 1980. The research method used is a qualitative method with 5W+1H data analysis to determine the point of view and perspective used in the storyline. The stages of documentary film production start from research, data collection, data analysis, creating a story synopsis, writing a treatment script, production and then the editing process for the Parsan film. This research aims to design a documentary film that depicts Parsan's life, as the figure behind the manual film poster paintings at the Rajawali Cinema, Purwokerto. The film aims to be a medium for appreciation of the figure of Parsan, who so far not many people know about his dedication. This documentary film has been screened at several film festivals, one of which was nominated at the NETPAC-Jogja Asian Film Festival and received a screening contract with BioskopOnline.id.